2013
DOI: 10.1016/j.micinf.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of IFITM, the newly identified IFN-inducible anti-HIV-1 family proteins

Abstract: IFN-inducible IFITM proteins (IFITM1, 2, and 3) inhibit the replication of various viruses including HIV-1 through poorly understood mechanisms. Here, we further analyzed characteristics of these newly identified HIV-1 restriction factors. Firstly, in contrast to other anti-HIV-1 proteins, such as tetherin and APOBEC3G, IFITMs were resistant to a down-regulation of surface expression or degradation by HIV-1 proteins. Secondly, the enforced expression of IFITMs reduced the production of HIV-1 viruses from cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 42 publications
5
60
0
Order By: Relevance
“…More recently it has been shown that IFITMs, particularly IFITM2 and IFITM3, colocalize with Env and Gag proteins and can be incorporated into nascent virions, which can impair fusion to target cells (61,62). IFITMs have relatively modest HIV-suppressive activity, and it is hypothesized that these proteins act in part by interfering with viral protein production (63). The NL4-3 strain of HIV has been reported to be resistant to inhibition by full-length but not C-terminally truncated IFITM1, potentially due to differential cellular localization of the two IFITM1 protein species (64).…”
Section: Discussionmentioning
confidence: 99%
“…More recently it has been shown that IFITMs, particularly IFITM2 and IFITM3, colocalize with Env and Gag proteins and can be incorporated into nascent virions, which can impair fusion to target cells (61,62). IFITMs have relatively modest HIV-suppressive activity, and it is hypothesized that these proteins act in part by interfering with viral protein production (63). The NL4-3 strain of HIV has been reported to be resistant to inhibition by full-length but not C-terminally truncated IFITM1, potentially due to differential cellular localization of the two IFITM1 protein species (64).…”
Section: Discussionmentioning
confidence: 99%
“…To interpret the functional impact of the changes observed it is important to keep in mind that: IFIT1 and IFIT3 are both implicated to function against viral infections (19); OASL functions in antiviral response (20); AZU1 serves as an important mediator during the initiation of the immune response (30); and APOBEC3G promotes cytidine deaminase-dependent DNA repair to render radiation resistance in lymphoma (48). In addition, IFN-inducible IFITM proteins (IFITM1, 2 and 3) inhibit the replication of various viruses including HIV-1 (21). Therefore, functions of the single-dose treatment gene signature support the fact that few genes are implicated in eliciting an immune response that could possibly be exploited with immunotherapy or vaccination to harness the tumor cell mediated immunogenic events.…”
Section: Discussionmentioning
confidence: 99%
“…An overexpression screen of interferon-stimulated genes revealed that IFITM3 and perhaps IFITM2 can control HIV-1 [20]. Further in vitro studies using overexpression of IFITM1-3 and depletion of these proteins by RNA interference substantiated the evidence that these proteins are HIV-1 restriction factors [2123]. Consistent with the notion that IFITM3 restricts RNA virus infection by blocking fusion [24, 25], it is believed that IFITM3 and IFITM2 proteins also inhibit fusion of HIV-1 [21, 22].…”
Section: Restriction Of Hiv-1 At the Membranementioning
confidence: 99%